Improved professional practices in social services through Emotional Labor strategies - Gvelesiani, Tea; Sadzaglishvili, Shorena; Gigineishvili, Ketevan; Lekishvili, Ketevan; Namitcheishvili, Salome (Frontiers in Psychology, 2023)
The present study provides analyses of Emotional Labour (EL) and its consequences for practitioner social workers in Georgia. The mixed methods study comprised of two stages. Firstly, qualitative study was conducted to determine the organizational characteristics defined by practitioner social workers (N=70). Secondly, quantitative study was examined among the members of Georgian Association of Social Workers (N=165) to determine the direct and indirect influences of organizational characteristics between EL and work outcomes: Personal Accomplishment and Burnout. The results are pragmatic and applicable for social service provider organizations to gain positive results on the individual and organizational levels.